The important function and training of sensitive quality in basketball method research - Song, P.; Wu, X.; Lian, X. G.; Jia, Y. (Mathematical Problems in Engineering, 2022)
Basketball is a skill-oriented group sport, which has been popularized and developed in China. However, the research on physical fitness training of basketball in China mostly focused on strength quality and speed quality, and less research was done on sensitive quality. Based on this, this paper aims to explore the important role of agility in basketball and put forward reasonable and scientific training suggestions in order to enrich the content of basketball training, complete the training system and to improve the level of basketball players as a whole.